1993
DOI: 10.3109/02841869309096113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients with Nasopharyngeal Carcinoma

Abstract: From 1971 to 1985 a total of 122 patients with non-distant metastatic nasopharyngeal carcinoma were treated at the Norwegian Radium Hospital with radiation doses that increased from 50 Gy (at 2 Gy/fractions) to 70 Gy (at 2 Gy/fractions) during the treatment period. Possible relationship between the increase in dose and survival time was investigated. The median cancer-specific survival time was 50 months, and the median crude survival time 38 months. No correlation was found between radiation dose and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…Except for histology (ICD-O-3 code) records, SEER database also recorded the tumor differentiation grade, a much simpler system. Compared to differentiated squamous and non-keratinizing carcinoma, undifferentiated cancer has a significant better survival prognostics due to its high sensitivity to RT and chemotherapy [29]. Table 3 showed that in moderately-differentiated subgroup, surgery patients had significantly lower risk of cancer-specific death than non-surgery group (HR = 0.36, 95% CI 0.16–0.82, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Except for histology (ICD-O-3 code) records, SEER database also recorded the tumor differentiation grade, a much simpler system. Compared to differentiated squamous and non-keratinizing carcinoma, undifferentiated cancer has a significant better survival prognostics due to its high sensitivity to RT and chemotherapy [29]. Table 3 showed that in moderately-differentiated subgroup, surgery patients had significantly lower risk of cancer-specific death than non-surgery group (HR = 0.36, 95% CI 0.16–0.82, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…We included different histologic subclassification groups of WHO tumors; 60 nonkeratinizing carcinomas and nine keratinizing squamous cell carcinomas. Even though the two groups showed different biologic features in many aspects 47, 48, there have been some controversial reports about the difference of OS or treatment response between the two groups according to different geography and different race 49–52. And even the distribution of histologic types and the biologic features of each groups varied with geography 49, 53.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports concerning consecutive series are more likely to reflect the actual effectiveness of treatments in clinical practice and have provided useful information on a number of other clinical issues, including the impact on outcome of evolving imaging and radiation treatment techniques. Individual institutional reports of patients treated with conventional RT have been published over the past 4 decades (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and have shown a trend for improvement of outcome with time. Most recent reports from North America have shown local control rates approaching 100% and 5-year overall survival (OS) rates approaching 90% after three-dimensional (3D) conformal or intensity-modulated RT (IMRT) (16,17).…”
Section: Introductionmentioning
confidence: 99%